2022
DOI: 10.4102/ojvr.v89i1.1954
|View full text |Cite
|
Sign up to set email alerts
|

Human and animal fasciolosis: coprological survey in Narok, Baringo and Kisumu counties, Kenya

Abstract: Fasciolosis is caused by digenean trematodes of the genus Fasciola. The principal definitive hosts are cattle, sheep and goats. Humans are infected as accidental hosts. Fasciolosis is one of the major neglected tropical diseases and is considered an emerging zoonotic infection. This study was aimed at determining the prevalence of human and domestic animal fasciolosis in selected counties in Kenya. Stool samples for Fasciola diagnosis were collected from humans and domestic animals and transported to the labor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 18 publications
1
6
0
1
Order By: Relevance
“…In the current study, positive rate of infection showed that no significant variation was found between females and males [18,37,38]. These findings means that either F. hepatica does not associated with sex of animals [23], or both sexes exposed to the same risk factor of infection such as contaminated grass [39].…”
Section: Epidemiological Risk Factorsmentioning
confidence: 56%
“…In the current study, positive rate of infection showed that no significant variation was found between females and males [18,37,38]. These findings means that either F. hepatica does not associated with sex of animals [23], or both sexes exposed to the same risk factor of infection such as contaminated grass [39].…”
Section: Epidemiological Risk Factorsmentioning
confidence: 56%
“…would prioritize nutrition from intake feed for immunity and, thus, decreased energy storage leading to lower BCS ( Levi et al ., 2020 ). Association of low BCS to cattle fasciolosis was also reported in Nigeria ( Shinggu et al ., 2019 ), Kenya ( Kipyegen et al ., 2017 ), and Pakistan ( Khan et al ., 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…El riesgo de intoxicación por micotoxinas en los cuyes fue evaluado a partir de los valores de la Tabla de asociación tetracórica de 2×2 simple de estrato único (TABLA II), a fin de analizar 2 variables dicotómicas: una independiente (exposición) y una dependiente (enfermedad), donde las micotoxinas se manifiestan con enfermedad en los animales [27].…”
Section: Determinación De Las Variables De Estudiounclassified